2012
DOI: 10.2134/jeq2011.0308
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous Oxide Emission from Riparian Buffers in Relation to Vegetation and Flood Frequency

Abstract: The nitrate (NO(3)(-)) removal capacity of riparian zones is well documented, but information is lacking with regard to N(2)O emission from riparian ecosystems and factors controlling temporal dynamics of this potent greenhouse gas. We monitored N(2)O fluxes (static chambers) and measured denitrification (C(2)H(2) block using soil cores) at six riparian sites along a fourth-order stretch of the White River (Indiana, USA) to assess the effect of flood regime, vegetation type, and forest maturity on these proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 42 publications
2
44
0
Order By: Relevance
“…Jacinthe et al (2011) found that in mature riparian forest during frequent flooding (four to six times per year), the mean N 2 O flux was significantly higher than that during occasional floods (2-3 # year −1 ) or rare floods (every 20 year), whereas the magnitude of the flux was higher after short-duration than after long-duration floods.…”
Section: Nitrous Oxidementioning
confidence: 88%
See 1 more Smart Citation
“…Jacinthe et al (2011) found that in mature riparian forest during frequent flooding (four to six times per year), the mean N 2 O flux was significantly higher than that during occasional floods (2-3 # year −1 ) or rare floods (every 20 year), whereas the magnitude of the flux was higher after short-duration than after long-duration floods.…”
Section: Nitrous Oxidementioning
confidence: 88%
“…Jacinthe et al (2011) found that large pulses of N 2 O emission (up to 80 mg N 2 O m −2 day −1 ) occurred after flood events, but the magnitude of the flux enhancement varied depending on the flood event, being higher after short-duration than after longduration floods. They also found that the effect of forest maturity and vegetation type on N 2 O emission was not significant (Jacinthe et al 2011).…”
Section: Introductionmentioning
confidence: 95%
“…Past studies have shown that flood history affect riparian vegetation community composition (Catford et al, 2011;Rotkin-Ellman et al, 2004), and the distribution of sediment, organic matter and nutrients across riparian landscapes (Blazejewski et al, 2009). Flood frequency was also found to have both short-term and long-term effects on the nitrous oxide-producing capacity of riparian soil (Jacinthe et al, 2012). In light of the foregoing, it is hypothesized that flood frequency determines the dynamics of trace gases in riparian buffers, with higher emission rates expected in flood-impacted than in flood-protected riparian areas.…”
Section: Introductionmentioning
confidence: 97%
“…Denitrification and increased N 2 O production is enhanced by high soil water contents (Machefert and Dise, 2004;Maag and Vinther, 1996), although the frequency and duration of flooding may also be important. In riparian systems, a shorter flooding duration correlated with the highest N 2 O emissions, which diminished the longer the period of inundation (Jacinthe et al, 2012). In addition to water availability, temperature is also recognised as an important variable in determining the production and consumption of N 2 O and CO 2 via its effects on the metabolic activity of microorganisms and plants (Davidson and Janssens, 2006;Butterbach-Bahl et al, 2013;Kirwan et al, 2014;Kim et al, 2015).…”
Section: Introductionmentioning
confidence: 99%